Perancangan Sistem Informasi Perpustakaan di SMP Negeri 1 Baros Berbasis Web Menggunakan Framework Laravel - Ilham, Ilham Rizqi; Sigit Auliana; Nurul Chapid; Gagah Dwiki Putra Aryono (STMIK PONTIANAK, 2025)
The rapid development of information technology is encouraging various educational institutions to adopt digital-based systems to improve service efficiency. At SMP Negeri 1 Baros, manual library management has resulted in ineffective processes for member data collection, book collection records, borrowing, returning, and reporting. This research aims to design and build a web-based library information system using the Laravel framework to streamline library administration processes. The development method used is the Waterfall method, starting with needs analysis, design, implementation, testing, and system evaluation. The tools used include Laravel, MySQL, and XAMPP. The results of the study indicate that the developed information system can improve efficiency, accuracy, and ease of library management, while providing more flexible access to library services for students, teachers, and librarians.